Faktor-Faktor Yang Mempengaruhi Realisasi Penerimaan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan (PBB-P2) Di Kecamatan Dendang Kabupaten Tanjung Jabung Timur - Tri Sugiharto; Elyanti Rosmanidar; Nurfitri Martaliah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Abstract The purpose of this study was to determine and analyze the effect of PAD (X1), number of taxpayers (X2), number of residents (X3), number of regions (X4) and GRDP (X5) simultaneously and partially influencing PBB-P2 revenue in the District. Dendang, Dendang District, East Tanjung Jabung Regency. This type of research is quantitative with panel data in the period 2017-2021. The data analysis used is panel data regression. The results showed that the statistical value in this study was 12.43099 (Fcount > Ftable = 2.49), while the probability value was 0.000 (P<0.05). This means that simultaneously PAD (X1), number of taxpayers (X2), total population (X3), number of regions (X4) and GRDP (X5) have a significant effect on PBB-P2 revenue in Kandis City Village, Dendang District, Tanjung Jabung Regency East. Partially, PAD has a tcount of -3.051742 with a ttable value of 1.68957 (tcount > ttable), while the probability value is 0.0057 (P<0.05). This means that partially, PAD has a significant effect on PBB-P2 revenue in Dendang District. The conclusion of PAD (X1) partially on PBB-P2 revenue in Dendang District, East Tanjung Jabung Regency, while the number of taxpayers (X2), population (X3), number of regions (X4) and GRDP (X5) partially have no effect on revenue PBB-P2 in Dendang District, East Tanjung Jabung Regency.